Strategy Analysis of Eclipse Hotel Yogyakarta During the Covid-19 Pandemic on Market Segmentation Changes - Mutiara Ramadhani, Sekar; Abdurrahman, Agus (International Journal of Science, Technology & Management, 2023)
The tourism sector is a sector that can increase regional income. Tourism opens up business opportunities and employment opportunities for people in the area. However, in early 2020, the world was shocked by the covid-19 virus outbreak, which hit the world of the tourism industry and the creative economy in Indonesia. Eclipse Hotel Yogyakarta is one of the star hotels in the Prawirotaman Street area of Yogyakarta that was affected. This research aims to find out how Eclipse Hotel Yogyakarta’s strategy adapts to changes in the customer market during the covid-19 pandemic. The research method used is qualitative. This approach involves the use of data collection techniques based on interviews with Eclipse Hotel Yogyakarta employees and observations made during internships at the hotel. The data collected from the interviews will be analyzed using the content analysis method. The results obtained in this study are the COVID-19 pandemic has an influence on changes in market segmentation and has an impact on marketing strategies and service adjustments at Eclipse Hotel Yogyakarta made to meet the needs of market segments before the pandemic. The marketing strategy carried out by Eclipse Hotel Yogyakarta is to use social media increase customers.